Humanised monoclonal antibody therapy for rheumatoid arthritis. - Isaacs, J; Watts, R; Hazleman, B; Hale, G; Keogan, M; Cobbold, S; Waldmann, H (1992)
Monoclonal antibodies that target T cells have shown some benefit in rheumatoid arthritis although responses have not been long lasting. This is partly due to insufficient therapy consequent upon antibody immunogenicity. Use of humanised antibodies, which are expected to be less foreign to man than conventional rodent antibodies, might overcome this problem. We therefore assessed in a phase 1 open study the potential of a "lymphocyte depleting" regimen of the humanised monoclonal antibody CAMPATH-1H in 8 patients with refractory rheumatoid arthritis. Apart from symptoms associated with first infusions of antibody, adverse effects were negligible. Significant clinical benefit was seen in 7 patients, lasting for eight months in 1. After one course of therapy, there was no measurable antiglobulin response, although 3 out of 4 patients have become sensitised on retreatment. Humanisation reduces the immunogenicity of rodent antibodies but anti-idiotype responses may still be seen on repeated therapy, even in patients sharing immunoglobulin allotype with the humanised antibody.